Ensino de tópicos de Geometria Analítica com auxílio de planilhas eletrônicas - Antunez, Kelly Kananda Teixeira (2021)
The National Curriculum Common Base (BNCC) ensures that is the student’s right to understand the digital information and communication technologies to use them in their social practices. Aiming to contemplate such rights and recognizing the importance to work with active methodologies to stimulate the interest and autonomy from the student, we elaborate and develop a methodological proposal. This proposal aimed the teach topics of Analytical Geometry with the support of Excel for students of the third grade of high school at “Col´egio Interativa” from the private school system of Foz do Igua¸cu city. For this, through bibliographical research, we elaborate a theoretical reference to meet the Brazilian government actions of incentive to use of technologies in education and to identify favorable or contrary conditions of such use in the teacher’s view. These claim that the use of technologies can encourage student’s reasoning and creativity, but also to reveal the precariousness of infrastructure or the lack of professional profissional. We also cite the first signs of the creation/discovery of Analytical Geometry and the guidelines of official documents, such as the BNCC and the Curriculum Guidelines for Basic Mathematics Education in Paraná (DCE), on the teaching of this geometry in Basic Education. These documents emphasize the importance of working with concepts such as distance between points, straight and circle equations and representations in the Cartesian system, which will allow the student to relate Mathematics with other areas of knowledge and recognize its applicability. To help understand the activities applied in the methodological proposal, we developed some topics of Analytical Geometry through definitions, propositions and theorems. The application of the proposal aimed to analyze the benefits of inserting technologies (electronic spreadsheet) in the development of contents of Analytical Geometry in High School, in addition to contributing to the social development of students and encouraging their participation in the process of knowledge construction. To assess these benefits, a comparison was made between diagnostic evaluation and evaluation after application of the proposed methodology. In addition, a questionnaire was applied to analyze if, in the student’s view, the methodology used helped in learning. The results obtained with the assessments were not satisfactory, which led us to consider possible difficulties in interpreting questions and in working with basic mathematics, given what the students said through the questionnaire. In this one, the students said that they increased their knowledge about Excel and that they understood the concepts worked. We realize that technologies can make classes more meaningful, however, against of obstacles such as lack of infrastructure and training, there is a need to think about public policies that provide what is necessary to ensure, in all its forms, quality education.